The Relationship Between The Post Trauma Stress Disorder And Covid-19 Incidence Among Uae Citizens; A Cross-Sectional Study (Journal of Namibian Studies : History Politics Culture, 2023)
COVID-19 psychologically shocked almost everybody in the world, caused millions of deaths, and corrupted every sector of our daily lives. And now after the pandemic, mostly minor studies show that this pandemic has serious effects on our daily lives in the long run. Whether traumatized Emirati university students remain unclear. This study aimed to investigate whether the posttraumatic stress disorder among Emirati students.: This study was performed on a sample of 37 citizens by a questionnaire they to fill, out at the Al Ain University in the United Arab Emirates. A total of thirty-seven participants were surveyed using questionnaires to assess post-traumatic stress disorder. The analysis of the collected data revealed a moderate level of PTSD symptoms and a moderate level of self-concealment. In conclusion, the existing literature has shown a correlation between posttraumatic stress disorder (PTSD) and COVID-19. Specifically, it has been reported that pupils who have contracted COVID-19 and exhibit emotional disturbances in their personalities are more susceptible to developing posttraumatic stress disorder. Consequently, it is imperative to provide psychological support to these individuals.